THE EFFECT OF SYSTEM PARAMETERS ON THE CONDENSATION PERFORMANCE OF HEAT PUMP SYSTEM USING R290 - Hocaoglu, S.; Ozkan, D. B. (YILDIZ TECHNICAL UNIV, 2018)
Since global warming has reached critical levels, limitations have been placed on the use of certain fluoride-containing refrigerants by F-Gas regulations. The EU F-Gas Regulation has introduced quotas for the use of refrigerants with a global warming potential(GWP) greater than 150. Hydrofluorocarbons(HFCs) from restricted refrigerants are widely used in heat pump systems. Considering the environmental impact of these refrigerants, it is important to look for long-term alternatives to comply with F-gas regulations. Hydrocarbon(HC) refrigerants are shown as suitable alternatives for heat pump applications. R290 as HC refrigerant is a potential refrigerant suitable for existing HFCs systems due to zero ODP and low GWP. In heat pump systems, there are many system components or parameters that are effective in condensing the air passing through the evaporator. It is very important to know how these elements affect the condensation performance in different design situations. In this study, the effect of different parameters such as capillary length, charge amount and evaporator tube volume on the condensation performance of a R290 hydrocarbon refrigerant heat pump was investigated by the experimental design approach. The experimental results obtained was compared with the theoretical model. It has been determined that the most effective parameter on the condensation performance is the capillary tube length with the effect of 35%.
Keywords: Heat Pump; Hydrocarbons; Propane; R290; F-Gas Regulation; GWP; ODP; LATTICE BOLTZMANN METHOD; HYDROCARBON REFRIGERANTS; TRANSFER IMPROVEMENT; FORCED-CONVECTION; REPLACE HFC-134A; WATER-HEATERS; PRESSURE-DROP; NANOFLUID; SIMULATION; MIXTURES; Thermodynamics